Web-Based Temperature, Oxygen Saturation, and Heart Rate Monitoring System - Richa Rachmawati, Yuli Yessy; Ayu Sanjaya, Yulia Putri; Edilia, Stevany (Pandawan Sejahtera Indonesia, 2022)
Heart rate and oxygen saturation is a tool designed to measure heart rate, oxygen level, and body temperature without any contact with the human body. It is mainly used to assess primary health conditions. Symptoms resulting from a heartbeat are abnormal conditions of tachycardia and bradycardia. Symptoms caused by oxygen levels are ARI and asthma, an irregular breathing condition. Symptoms of an abnormal heart rate and oxygen saturation may indicate disease. Therefore, we created a web-based heart rate and oxygen saturation monitoring system for this study. IoT (Internet of Things) is used to manufacture this tool. This tool is programmed with sensors such as the AMG8833 sensor, the MAX30102 sensor, and the ESP32 microcontroller as a data processor, and the data is sent via a Wi-Fi connection to be read from the sensor. Wirelessly to your website in real-time. The website displays sensor data sent wirelessly from the microcontroller and then stored in a web server database. This data collection or monitoring system makes it easier for us, especially medical personnel, to check the health and analyze the results of data stored in our web server database.